Contrast Experimental Study on the Dynamic Characteristic of Modification Gear - Yan Tianxiao; Zhang Ruiliang; Wang Tie; Shi Ruonan; Liu Yaqiong; Jiang Xiongfei (Jixie chuandong)
The meshing impact of gear is the main vibration source and noise source of automobile transmission and the meshing impact of gears can be effectively reduced through modification.In order to explore the influence of different parameters on the vibration and noise of gear,the contrast experimental study on the dynamic characteristic of the modification gear is carried out,and the suitable modification parameters are obtained.The experimental results provide basic data for determining the modification parameters of gear.